Balancing public and private sector roles in an effective seed supply system - Loch, D.S; Boyce, K.G (Elsevier, 2003)
A seed supply system can be defined in general terms as that combination of components, processes and their organisation, along with the interactions and support involved in the production and marketing of seeds of one or more species to a particular user–client grouping in an ongoing way. Seed supply systems come in a variety of forms, and operate at a range of levels (national, regional and local) and with different plant materials used for different purposes. In all cases, however, the public and the private sectors have complementary roles in ensuring that there is an effective seed supply system, which can meet consumer needs in terms of the range of plant materials available and the quantities and quality of seed required at an affordable price. Nationally, it is the government that sets the policy framework within which seed supply systems must operate, and also provides some supporting infrastructure. The private sector then is responsible for the timely and cost-effective production and delivery of seed to end users/clients within the policy framework that has been set by government. The balance in terms of public–private sector roles and responsibilities differs from place to place and changes over time. This paper discusses the factors that help shape what is an effective seed supply system under a particular set of circumstances, but one that may not necessarily be as effective in other countries/regions or with a different product mix. It also considers the forces that lead to a gradual evolution of the system over time and to recent and more radical changes in major developed countries. The latter shift has been brought about by the commercial opportunities presented by genetic engineering and legal protection of the intellectual property (IP) in new plant varieties, coupled with a shift in government policy towards deregulation of the economy (and so greater industry self-regulation in areas like quality assurance). These factors have led to far-reaching structural changes in relation to commercial seed production and delivery in the developed world over the past decade. The recent changes in seed supply arrangements were focused initially on high volume arable food crops in the larger developed economies of North America and western Europe. However, they are now gradually moving through to lower volume seed markets and to smaller, less developed economies where they will have different implications for the development of effective country-specific seed supply policies.